1972
DOI: 10.1080/00288233.1972.10430544
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid content of some barley varieties grown in New Zealand

Abstract: Eleven varieties of 2-row barley grown III New Zealand were analysed for 17 amino acids, ammonia, and nitrogen. The varieties were all grown in the one location, Halcombe, in the Rangitikei district of the North Island, and no artificial fertiliser was used. Samples were collected from harvests in two consecutive seasons (1966-67 and 1967-68), and the results were analysed for varietal and seasonal effects on amino acid composition of air-dry samples. Correlations, regressions. and y intercept values, with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It is important to note that the value of lysine, the most limiting essential amino acid in cereals, was 3.36 g/100 g protein in BK 306 was comparable to DWRUB 52 (3.49 g/100 g protein). Dingle and McEwan (1972) reported that proline and glutamic acid accounted for the major increases in amino acids with increasing protein content, and cystine also contributed to a significant extent. However, in the present study it was true for proline and glutamic acid, not for cystine.…”
Section: Comparison Of Amino Acid Composition Between Bk 306mentioning
confidence: 99%
“…It is important to note that the value of lysine, the most limiting essential amino acid in cereals, was 3.36 g/100 g protein in BK 306 was comparable to DWRUB 52 (3.49 g/100 g protein). Dingle and McEwan (1972) reported that proline and glutamic acid accounted for the major increases in amino acids with increasing protein content, and cystine also contributed to a significant extent. However, in the present study it was true for proline and glutamic acid, not for cystine.…”
Section: Comparison Of Amino Acid Composition Between Bk 306mentioning
confidence: 99%